2020
DOI: 10.1177/2151459320940959
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Readmissions After Total Hip Replacement in Octogenarians and Nonagenarians

Abstract: Introduction: As the US population ages, the need for total hip arthroplasty (THA) is predicted to increase by 174% by 2030. The purpose of our study was to examine the rate and risks of 30-day complications and unplanned readmission in patients over the age of 80 years old. Materials and Methods: The National Surgical Quality Improvement Project database for the years 2008 to 2014 was queried for patients over the age of 80 undergoing THA. The risks of major complications, minor complications, bleeding occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The literature on early outcomes of nonagenarians undergoing TJA is conflicting. Some studies report that elderly patients experience high complication rates following total hip arthroplasty (THA) [3,16] and total knee arthroplasty (TKA) [6,16,17], whereas others have found that such risks were low [2] and concluded that old age alone should not prevent patients from undergoing TJA if comorbidities are assessed and addressed [1,7,8]. Methodological limitations to previous studies include using 30-day follow-up data [6,16,17], not using controls [2,3,16], or grouping nonagenarians with patients of other decades prior to analysis [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The literature on early outcomes of nonagenarians undergoing TJA is conflicting. Some studies report that elderly patients experience high complication rates following total hip arthroplasty (THA) [3,16] and total knee arthroplasty (TKA) [6,16,17], whereas others have found that such risks were low [2] and concluded that old age alone should not prevent patients from undergoing TJA if comorbidities are assessed and addressed [1,7,8]. Methodological limitations to previous studies include using 30-day follow-up data [6,16,17], not using controls [2,3,16], or grouping nonagenarians with patients of other decades prior to analysis [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been reported that THA is a safe procedure for nonagenarians, with no increased rates of complications 8 . In contrast, other studies have shown that the risk of complications increases with age 5,9,10 . These results may be contradictory because most previous studies investigated small patient cohorts and thus were underpowered.…”
mentioning
confidence: 70%
“…Previous studies have suggested that age alone may be an independent risk factor for postoperative mortality and morbidity 3 . Nevertheless, the increased risk of complications and mortality within the elderly population may be confounded by preexisting comorbidities and frailty 4,5 .…”
mentioning
confidence: 99%
“…This was evident, although mean preoperative levels of hemoglobin were similar in all groups. Yohe et al recently reported elevated rates of transfusion for octogenarians undergoing THA, too [16]. Besides lower tolerance of anemia in the elderly, the indication for transfusion could have been made more frequently by the responsible physician since, for example, chronic HIV and hepatitis -possibly induced by transfusionmay not be of that much concern in geriatric patients.…”
Section: Discussionmentioning
confidence: 99%